Strategi peningkatan penghasilan petani lokal buah mangga brazilia di banjar dinas sanih kecamatan kubutambahan - Ni Nyoman Juli Nuryani; Apriliani, Ni Komang Trisna (Yayasan Baru Haji Samsudin, 2026)
Marketing strategy plays a crucial role in enhancing the competitiveness and added value of horticultural commodities, including Brazilia mangoes. Despite their superior product quality, local farmers in Banjar Dinas Sanih, Kubutambahan District, continue to face various marketing challenges that contribute to price fluctuations and unstable incomes. This study aims to analyze the marketing strategy of Brazilia mangoes based on the marketing mix framework, encompassing product, price, place, and promotion, as well as to identify the marketing constraints encountered by local farmers. A qualitative approach employing a case study design was adopted. Informants were selected using purposive sampling, while data were collected through in-depth interviews, direct observation, and documentation. Data were systematically analyzed through data selection and organization, descriptive presentation of the findings, and interpretation to derive meaningful conclusions. The credibility of the findings was enhanced through source triangulation to verify the consistency of information obtained from different informants. The results indicate that product quality constitutes the primary competitive advantage of Brazilia mangoes, as they are characterized by large fruit size, thick flesh, a sweet taste, a distinctive aroma, and relatively good shelf life, all of which contribute to strong consumer appeal. However, pricing strategies remain largely dependent on market mechanisms, distribution channels continue to rely predominantly on collectors and traditional markets, and promotional activities have not yet fully utilized digital media. In addition, farmers face several challenges, including price fluctuations, changing weather conditions, high production and maintenance costs, and limited marketing networks. The study concludes that the implementation of the marketing mix has supported the marketing of Brazilia mangoes; however, further improvements are needed through product innovation, expansion of distribution networks, and optimization of digital promotion strategies to enhance competitiveness and ensure the sustainability of local farming enterprises.